Inequality of Opportunity : Reply to Pedro Rosa Dias and Erik Schokkaert - Kanbur, Ravi (Wiley, 2015)
We welcome the comments of Pedro Rosa Dias and Erik Schokkaert on our Editorial as a means of stimulating further debate on the usefulness of estimates of inequality of opportunity, especially for policy purposes. Our responses to their comments are in three categories. First, they broadly agree with many of our criticisms of the Paes de Barros et al. approach to measuring inequality of opportunity, but they say that these criticisms are already well appreciated in the literature. We beg to differ. Given our knowledge of work in policy settings, we believe that strong health warnings are in order. Second, we feel they do not sufficiently engage with a number of our points, including on talent and on luck. Third, while we agree with them that a strong focus on the income–health gradient leaves out many other considerations, we would nevertheless continue to argue for this focus on pragmatic grounds in the realm of policy. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions. http://olabout.wiley.com/WileyCDA/Section/id-820227.html